Participatory Banks Serving Morocco’s New Development Model: Opportunities, Challenges and Perspectives (Global Journal of Human-Social Science, 2025)
The aim of this research is to analyse the effect of participatory banks on the success of Morocco s new development model This work aims to analyse theoretically and empirically the relationship between participatory banking and the success of this new model Banking and financial systems influence the success of this new development model through their functions such as mobilizing funds for profit financing sustainability mobilizing alternative financing mechanisms combining the profitability and financing of projects with strong social and environmental impacts creating wealth and quality employment opportunities creating new synergies to attract private investment promote job creation and provide opportunities for growth The results obtained lead us to conclude that there is a positive contribution between the participatory banking industry and the success of this new development model
Keywords: banks; morocco’s new development model; banking and financial systems; economic growth; social development